Research on Seismic Resistance of Precast Concrete Shear Walls with Bolt Splicing - XU Zhuang; ZHANG Ruigang (Renmin Zhujiang)
A design scheme of fully-assembled precast concrete shear walls with unit components spliced by bolts is proposed for the prefabricated unit residence system.An integral precast wall and two overlapped precast ones (consisting of two thin panels spliced horizontally by bolts) are designed,and low-cycle static loading tests of the walls under the bend-shear coupled loading mode are performed to study the seismic resistance of the structures.The research results indicate that the failure mode of the overlapped wall is the same as that of the integral one,and the crack development of the wall body is insufficient.The bearing capacity of the overlapped wall is equivalent to that of the integral one.The former is more ductile,whose displacement ductility factor is about 1.1 times that of the latter.The initial stiffness of the integral wall is larger than that of the overlapped one,but the former's stiffness degrades faster.In addition,the quantity and locations of bolts have little effect on the energy dissipation capacities of overlapped walls,and joint connection might be the only function of bolts for overlapped walls.